Characterization of polylactic acid/halloysite nanotubes bionanocomposite films as food packaging films - Risyon, Nazratul Putri (2017)
In this work PLA/HNTs bionanocomposite films at varying concentration of HNTs (0.0, 1.5, 3.0, 4.5 and 6.0 wt.%) were produced to replace the commercialized food packaging materials in industry that are usually made-up of non-biodegradable material. Bionanocomposite films were prepared by casting method using polylactic acid (PLA) as biopolymer and halloysite nanotubes (HNTs) as the nanofiller producing PLA/HNTs bionanocomposite films. The neat PLA and PLA/HNTs bionanocomposite films were investigated regarding the dispersion of HNTs in the PLA films, chemical bonding between HNTs and PLA as well as molecular weight of PLA. The effects of HNTs concentrations on the mechanical, thermal, barrier and optical properties were investigated. Demonstration on the PLA films for food packaging application also conducted by studying the firmness and weight loss of tomato cherries that packaged with the films. It was found that HNTs were well dispersed in 3.0 wt.% PLA/HNTs bionanocomposite films while agglomeration of HNTs occurred in 6.0 wt.% PLA/HNTs bionanocomposite films indicated by the particle distribution histogram and TEM images. Hydrogen bond was formed between HNTs and PLA as proven from TEM analysis. The weight of average molecular weight (Mw) of PLA film incorporated with 3.0 wt% HNTs were lower than PLA film incorporated with 6.0 wt.% HNTs while number of average molecular weight (Mn) of 3.0 wt.% PLA/HNTs bionanocomposite films were higher than 6.0 wt.% PLA/HNTs bionanocomposite films. 3.0 wt.% PLA/HNTs bionanocomposite films were found able to exhibit the optimum mechanical properties in terms of tensile strength, yield strength and Young’s modulus due to the well dispersion of HNTs in the PLA matrix thus forming a stable hydrogen bond between HNTs particles and PLA molecules. This condition also due to the high average molecular number (Mn) which was 3.97 x 104 and polydispersity index (PDI) which was 1.97. At 3.0 wt.% PLA/HNTs bionanocomposite films also exhibit the lowest water vapor permeability (WVP) and oxygen transmission rate (OTR) compared to other concentration of PLA/HNTs bionanocomposite films due to the formation of tortuous path resulted from well dispersed HNTs in the PLA matrix. Meanwhile, incorporation of 3.0 wt.% HNTs in PLA matrix resulted to the optimum improvement in heat stability of the films by increasing the resistance of the films towards phase changes when heat was applied. Films transparency analysis revealed that there was no significant (p>0.05) change in the transmittance of light of the films when HNTs was added into PLA matrix. Based on the obtained results, the optimum concentration of HNTs in PLA that resulted to improvement in mechanical, thermal and barrier properties was found to be at 3.0 wt%. Demonstration on the tomato cherries’ firmness and weight loss indicated that the PLA film incorporated with HNTs able to extend the shelf life of the packaged tomato cherries due to improved mechanical, thermal and barrier properties of the film. In conclusion, the well dispersed of HNTs in PLA matrix, stable hydrogen bond between HNTs and PLA as well as high Mn and low Mw of PLA improved mechanical, thermal and barrier properties of PLA/HNTs bionanocomposite film. Addition of HNTs in PLA film able to prolong the shelf life of tomato cherries packaged with PLA/HNTs bionanocomposite film. Molecular weight analysis and demonstration of the PLA/HNTs bionanocomposite film is considered as the novelties of this work.